PREVALENCE OF ROOT STUMPS IN GERIATRIC PATIENTS - M., P.Induja; Dhanraj,; Surendar, (International Journal of Psychosocial Rehabilitation, 2020)
BACKGROUND: Tooth loss leads to the most significant oral health-related negative quality of life for the elderly. Due to the increasing life expectancy of the dentition, geriatric patients are experiencing a lot of oral health problems, putting them at higher risk.AIM: The aim of this study was to assess the prevalence of root stumps in geriatric patients.MATERIALS AND METHODS: A retrospective study was conducted using the records of the patients. Overall, 149 case sheets were reviewed, which were dated between June 2019 and March 2020. The data was collected from the patient records of Saveetha Dental College and hospitals. Data was recorded in Microsoft excel and later exported to IBM SPSS (version 20.0, Chicago, USA) and subjected to Statistical analysis The statistical analysis between age, gender, and tooth number was carried out in SPSS software. A chi-square test was done to compare the parameters. The outcome was represented in the form of bar charts.Results: Age groups were divided into 56-65, 65-75, and 75-85. Patients of age group 55-65 had 57.7%, 65-75 years of age had 37.9%, and 75-85 years of age had 5.34% of the total proportion of root stumps. More number of root stumps were diagnosed in the age group of 55-65 years, both male and female; however, it is not statistically significant. (Pearson Chi square test: P = 0.294, P > 0.05). Male patients had more root stumps when compared to females.Conclusion: Within the limits of the study, the age and gender of the patients who were diagnosed with root stumps were negatively correlated. A higher number of root stumps was diagnosed in males when compared to females, and the most frequent anatomical sites were right molars in geriatric patients.